Clean development mechanism : building international public-private partnerships under the Kyoto Protocol : technical, financial and institutional issues - Stewart, Richard...[et al] (UN New YorkUS, 2000)
Examines a number of issues and options for the design and operation of the Clean Development Mechanism (CDM).